Feasibility Study on Preparation of EN-GJL-250 Rough Microstructure Hydrophobic Surface by WEDM - Li, Zhaolong; Liu, Yingtao; Cao, Binren; Zhu, Bo; Yang, Xiaodong (Recent Patents on Engineering, 2023)
Background: Preparation of the superhydrophobic surface on the metal substrate can effectively solve the problems of easy corrosion and easy ice coating of metal materials, and it is given the functions of self-cleaning, oil-water separation, lubrication and drag reduction. Constructing micro-nano rough structures and reducing surface potential energy are the key factors in preparingsuperhydrophobic surfaces. There is no macroscopic cutting force between the electrode and workpiece in the WEDM process, the surface roughness can be changed by controlling the energy, and the complex shape can be manufactured by increasing the degree of freedom. The WEDM method has broad application prospects in the preparation of the superhydrophobic surface. Objective: To verify the feasibility of preparing the hydrophobic surface by WEDM, the micro-nano structure of the EN-GJL-250 (Gray cast iron material) surface was processed by the WEDM method, and the effect of surface roughness on the hydrophobicity of the surface was studied; Simultaneously, in the process of WEDM, the effects of peak current and pulse width on the surface roughness and static contact angle (CAs) of the EN-GJL-250 were studied. The purpose was to improve and control the surface hydrophobicity of the EN-GJL-250. Methods: The micro-nano structure was fabricated on the EN-GJL-250 surface by WEDM. Using the single factor test, by setting different peak currents and pulse widths, the surface roughness and CAs of the processed EN-GJL-250 can be measured. Results: Using the WEDM machine tool, by inserting set dimensions and regular contour parameters, the micro-nano structure with hydrophobic properties can be machined on the EN-GJL-250 surface. Different WEDM processing parameters produce rough microstructures of different scales and affect the hydrophobicity of the EN-GJL-250 surface. Experimental results show that with the increase of pulse width and peak current, the surface roughness of EN-GJL-250 also increases, and the number and size of craters in the microstructure increase, which improves the hydrophobicity of the surface of EN-GJL-250; When the peak current is 16A and the pulse width is 32us, the CAs of the prepared EN-GJL-250 surface is the highest. Conclusion: The surface roughness microstructure of EN-GJL-250 is processed by WEDM, which can realize the hydrophobicity of the surface. The pulse width and peak current will affect the roughness of the processed surface, thereby affecting the hydrophobic properties of the surface. The research data in this paper provides theoretical support for the industrial production of superhydrophobic EN-GJL-250 surfaces.
Keywords: surface roughness